Characterisation of the broad substrate specificity 2-keto acid decarboxylase Aro10p of Saccharomyces kudriavzevii and its implication in aroma development. Issue 1 (December 2016) - Stribny, Jiri; Romagnoli, Gabriele; Pérez-Torrado, Roberto; Daran, Jean-Marc; Querol, Amparo
Abstract Background The yeast amino acid catabolism plays an important role in flavour generation since higher alcohols and acetate esters, amino acid catabolism end products, are key components of overall flavour and aroma in fermented products. Comparative studies have shown that otherSaccharomyces species, such asS. kudriavzevii, differ during the production of aroma-active higher alcohols and their esters compared toS. cerevisiae . Results In this study, we performed a comparative analysis of the enzymes involved in the amino acid catabolism ofS. kudriavzevii with their potential to improve the flavour production capacity ofS. cerevisiae . In silico screening, based on the severity of amino acid substitutions evaluated by Grantham matrix, revealed four candidates, of whichS. kudriavzevii Aro10p (SkAro10p) had the highest score. The analysis of higher alcohols and esters produced byS. cerevisiae then revealed enhanced formation of isobutanol, isoamyl alcohol and their esters when endogenousARO10 was replaced withARO10 fromS. kudriavzevii. Also, significant differences in the aroma profile were found in fermentations of synthetic wine must. Substrate specificities of SkAro10p were compared with those ofS. cerevisiae Aro10p (ScAro10p) by their expression in a 2-keto acid decarboxylase-nullS. cerevisiae strain. Unlike the cell extracts with expressed ScAro10p which showed greater activity for phenylpyruvate, which suggests this phenylalanine-derivative to be the preferred substrate, the decarboxylation activities measured in the cell extracts with SkAro10p ranged with all the tested substrates at the same level. The activities of SkAro10p towards substrates (except phenylpyruvate) were higher than of those for ScAro10p. Conclusions The results indicate that the amino acid variations observed between the orthologues decarboxylases encoded bySkARO10 andScARO10 could be the reason for the distinct enzyme properties, which possibly lead to the enhanced production of several flavour compounds. The knowledge on the important enzyme involved in higher alcohols biosynthesis byS. kudriavzevii could be of scientific as well as of applied interest.